Sufism Discourse On Imam Al Shatibi's Maqashid Reasoning Paradigm - Asep Ahmad Arsyul Munir; Arif Tasrikin Imron (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2025)
Sufism as the spiritual treasure of Islam is often debated regarding its understanding within the framework of sharia. The maqasid (objectives) paradigm of rational thought by Imam Al-Shatibi, which emphasizes the purposes and wisdom behind Islamic laws, provides a valuable perspective. The purpose of this writing is to explore Sufism through the maqasid paradigm to ensure its conformity with the principles of sharia. The method used is a literature review and critical analysis of Sufi principles such as makrifat (gnosis), tazkiyat an-nafs (self-purification), and zuhd (asceticism) through the lens of maqasid. The research results show that maqasid serves as a solid foundation for Sufism to provide profound substantive meaning and prevent deviations. Maqasid also provides a framework for evaluating Sufi practices and their contextualization in modern life without sacrificing its core values. In conclusion, Al-Shatibi's maqasid paradigm ensures that Sufism is not only a profound spiritual practice but is also in line with Islamic sharia, enriching the spiritual dimension, and addressing the modern human need for authentic spirituality with a way of life in accordance with the objectives of sharia.